Towards human-centered design of supermarket checkout counter - Silva, Tânia Micaela Teixeira (2023)
Work-related muculoskeletal disorders (WMSD) pose a signifucant concern for supermarket cashiers, often stemming from the adoption of uncomfortable postures ant the performance of repetitive motions and manual material handling tasks. This study aimed to evaluate the risk of WMSD in supermarket cashiers and contribute to the development of new chekout counter designs. To achieve this goal, two separate studies were conducted. In the first study, the risk of WMSD was assessed by observing all tasks performed at two distinct chekout counters, using na inertial motion capture system – Xsens. The study involved 5 female cashiers from a supermarket situated in Northern Portugal, with ages ranging from 19 to 61 years old. The results revealed that various tasks carried a risk of WMSD, underscoring the necessity for a redesign of supermarket checkout setups to ease the physical strain experienced by cashiers. In the second study, anthropometric data was gathered from 155 employees working at the same supermarket. This group comprised 117 women and 38 men, with ages spanning from 18 to 64 years. The extensive dataset encompassed 28 static anthropometric measurements for each participant, as well as additional anthropometric data deemed pertinente for characterizing this population, such as body fat, boné mass, total body water, visceral fat, body mass (BM) and body mass index (BMI). The study unveiled a noticeable trend of growth within the population. These results emphasize the urgente need for a review of Portuguese anthropometric data and the adoption of effective ergonomic workplace design practices. In the future, collected data will be used to develop guidelines for new checkout designs.